Genomic comparison between Xanthomonas oryzae pv.oryzae and Xanthomonas oryzae pv.oryzicola,usingsuppression-subtractive hybridization - Soto Suárez, M.; González, C.; Piegu, B; Tohme, Joseph M.; Verdier, Valerie M. (Oxford University Press, 2010)
Xanthomonas oryzae pathovar oryzae (Xoo) and X. oryzae pv. oryzicola (Xoc) cause bacterial diseases in rice: leaf blight and leaf streak, respectively. Although both the Asian and the African strains of Xoo induce similar symptoms, they are genetically different, with the African Xoo strains being more closely related to the Asian Xoc. To identify the sequences responsible for differences between African and Asian Xoo strains and their relatedness to Xoc strains, a suppression-subtractive hybridization (SSH) procedure was performed, using the African Xoo MAI1 strain as a tester and the Philippine Xoo PXO86 strain and Xoc BLS256 strain as drivers. A nonredundant set of 134 sequences from MAI1 was generated. Several DNA fragments isolated by SSH were similar to genes of unknown function, hypothetical proteins, genes related to the type III secretion system, and other pathogenicity-related genes. The specificity of various fragments was validated by Southern blot analysis. SSH sequences were compared with several xanthomonad genomes. In silico analysis revealed SSH sequences as specific to strain MAI1, revealing their potential as specific markers for further epidemiological and diagnostic studies. SSH proved to be a useful method for rapidly identifying specific genes among closely related X. oryzae strains.